Exploring key cognitive indicators for practical use by parents in community setting - Tjhin Wiguna; Rini Sekartini; Taufiq Fredrik Pasiak; Ray Wagiu Basrowi; Melissa Stephanie Kartjito (Indonesian Nutrition Association, 2023)
The identification of child development milestones, specifically cognitive abilities, requires parental/caregiver awareness and knowledge. With the existence of multiple cognitive abilities such as attention and focus, memory, language, psychomotor skills, logic, reasoning, decision-making, problem-solving, social/emotional, there are multiple indicators to measure children's cognitive abilities. Pediatricians are the most knowledgeable and trusted authority to routinely screen and monitor the development of healthy children. Therefore, it is crucial that parents understand their children's developmental milestones so if they encounter anomalies, they can immediately consult with the professionals. This review compiles recently published research and current knowledge to examine potential key indicators of cognitive development in infants and children that can be utilized by parents and communities in an easily understood manner.